0812 The Restless Sleeper: Associations Between Clinical Symptoms, Ferritin Level, And Limb Movements. (12th April 2019) - Ingram, David; Perry, Gayln; Ehsan, Zarmina; Al-Shawwa, Baha
Abstract: Introduction: Iron status is an important aspect of the evaluation of children with restless leg syndrome, periodic limb movement disorder, or clinically restless sleep. While there is clear data in adults to support this relationship, the data in children is less well established. We evaluated possible associations between iron status, clinically symptoms of restless sleep, and polysomnographic-derived limb movements during sleep in a large pediatric sample. Methods: This is a retrospective analysis of a single institution sleep program looking at all patients who underwent overnight polysomnogram, had ferritin test within 24 hours of doing the sleep study, and had completed parent-report sleep questionnaire over the course of 1 year. Those with sleep apnea (Central Apnea Index >5/hr or Obstructive Apnea Hypopnea Index >2/hr) were excluded. In addition, children who were taking medications that potentially could affect outcomes of interest were excluded (hypnotics, psychotropic medications, supplemental iron). Results: There were a total of 46 patients who qualified for inclusion. Mean age was 6.7 years (range 0-15 years). Ferritin levels were not significantly different between children with or without six possible parent-endorsed descriptors of restless sleep. Children described as having "repeated kicks of legs" during sleep had a significantly higher single limb movement index (10.1 +/-5.4 vs 6.7 +/- 3.0, p=0.02) and total limb movement index (15.1 +/- 7.3 vs 10.3 +/- 5.7, p=0.04); otherwise there were no significant associations between symptoms and limb movement indices. Conclusion: In this carefully screened sample of children, we found no significant association between ferritin level and any parent-reported symptom of restless sleep or limb movement index. We found that children with parent-reported "repeated kicks of legs" during sleep had increased single limb movement and total limb movement indices. Support (If Any): None